2016
DOI: 10.17795/whb-29603
|View full text |Cite
|
Sign up to set email alerts
|

Women Are More at Risk of Poor Mental Health: Mental Health of Spanish Nurses Measured by the GHQ-12

Abstract: Background: Mental health is one of the principal indicators of people's quality of life. One of the professions most commonly associated with mental health problems is nursing. Objectives: We analyzed mental health in a group of female and male nurses from a hospital in Madrid (Spain) to evaluate whether differences exist between the groups. Furthermore, there is an analysis regarding whether the variables affecting mental health in female nurses are different from those affecting male nurses. Patients and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…For example, in the study by Portero et al ( 38 ) conducted on 235 HES practicians and nurses from four Andalusian hospitals (southern Spain), 32.3% of professionals were found to have impaired mental health. Likewise, in another study carried out in a tertiary hospital in Madrid (central Spain), the differences are even more pronounced ( 39 ). In the present study, means of 3.73 (SD = 3.67) are found for the total sample in the GHQ-12, and it is striking that similar scores (3.96 [SD = 3.27]) were found in a study conducted on Japanese nurses following an earthquake in Japan in 2017 ( 40 ), unlike other studies such as that conducted by Sánchez-López et al ( 41 ), which compares mental health between female and male nurses obtaining mean scores of 2.28 (SD = 2.81) and 1.61 (SD = 2.45), respectively.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in the study by Portero et al ( 38 ) conducted on 235 HES practicians and nurses from four Andalusian hospitals (southern Spain), 32.3% of professionals were found to have impaired mental health. Likewise, in another study carried out in a tertiary hospital in Madrid (central Spain), the differences are even more pronounced ( 39 ). In the present study, means of 3.73 (SD = 3.67) are found for the total sample in the GHQ-12, and it is striking that similar scores (3.96 [SD = 3.27]) were found in a study conducted on Japanese nurses following an earthquake in Japan in 2017 ( 40 ), unlike other studies such as that conducted by Sánchez-López et al ( 41 ), which compares mental health between female and male nurses obtaining mean scores of 2.28 (SD = 2.81) and 1.61 (SD = 2.45), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…As in the general Spanish population, women refer to some mental health problems more often than men, 14.1 vs. 7.2%, figures below those found in the present study (42). This fact shows that Spanish nurses may have an increased risk of mental health problems, as compared to the general Spanish population (39). In addition, there are variables that can increase this risk such as being a woman, young (31), having a mediocre or poor perception of health, having low work commitment (34), and working in services with a high level of stress, as is the case of emergency services.…”
Section: Discussionmentioning
confidence: 98%
“…The 67 studies and four official documents were included in this review, these studies have been included and detailed in Table S1 [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies investigated with questionnaires to assess self-concept [ 2 , 6 , 8 , 10 , 12 , 16 , 27 , 35 , 37 , 38 , 56 , 64 , 65 , 67 , 70 , 71 ], self-perception [ 2 , 3 , 4 , 7 , 8 , 11 , 13 , 14 , 26 , 28 , 29 , 30 , 31 , 32 , 34 , 36 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 57 , 60 , 66 , 68 , 69 ], physical activity [ 2 , 9…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, psychophysical strain may be negatively associated with age, possibly because older employees have higher levels of resilience or they develop coping skills with age or experience [43,44]. Interestingly, the relationship between age and psychophysical strain might differ across gender [42,45]. Finally, with respect to the type of contract, past research has shown an association between temporary employment and psychophysical strain, although with some differences across studies [46][47][48][49].…”
Section: Job Demands and Resources Related To Safety At Workmentioning
confidence: 99%